2017
DOI: 10.1111/bcpt.12761
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Fc Region of a Human Anti‐oncostatin M Monoclonal Antibody for Higher Affinity to FcRn Receptor and Extension of Half‐life in Cynomolgus Monkeys

Abstract: The purpose of this study was to evaluate the pharmacokinetics (PK) of anti-oncostatin M (OSM) IgG1 monoclonal antibodies, CNTO 1119 and its Fc variant (CNTO 8212), which incorporates the LS(Xtend) mutation to extend terminal half-life (T ), after a single intravenous (IV) or subcutaneous (SC) administration in cynomolgus monkeys, and to predict human PK. In study 1, single doses of CNTO 1119 and CNTO 8212 were administered IV or SC at 3 mg/kg to cynomolgus monkeys (n = 3 per group). In study 2, single doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For two different cancer immunotherapeutic antibodies the LS mutant IgG1 inhibited tumor growth significantly better than the wildtype IgG1 (112). Since the initial description of the LS mutations, multiple groups have shown these mutations boost antibody half-life in cynomolgus macaques (120, 121) and rhesus macaques (119, 122). The LS mutations have been helpful in sustaining protection against HIV-1 infection in animal models (119, 122, 123).…”
Section: Improved Antibody Half-life Circulationmentioning
confidence: 99%
“…For two different cancer immunotherapeutic antibodies the LS mutant IgG1 inhibited tumor growth significantly better than the wildtype IgG1 (112). Since the initial description of the LS mutations, multiple groups have shown these mutations boost antibody half-life in cynomolgus macaques (120, 121) and rhesus macaques (119, 122). The LS mutations have been helpful in sustaining protection against HIV-1 infection in animal models (119, 122, 123).…”
Section: Improved Antibody Half-life Circulationmentioning
confidence: 99%
“…These two antibodies represent the sum of anti‐OSM therapeutic agents that have progressed into clinical investigation. However, evidence suggests that further OSM‐targeted assets are or were in preclinical development, including a fully human OSM‐targeting mAb (CNTO8212; Janssen) and two OSMR‐targeting mAbs (Biogen Idec, Patent WO2014/194274A2, 2014; and Raven Biotechnologies, Patent US7572896B2, 2009).…”
Section: Clinical Development Of Osm‐targeted Therapiesmentioning
confidence: 99%
“…These mutated genes were used to produce a phage display library , from which Fc fragments with mutations that conferred higher affinity for FcRn at pH 6.0 (early endosomal pH) were selected [50]. Subsequently, similar approaches, or molecular modeling based on structural data, have been used to generate human IgG (IgG1 or IgG4) variants with increased affinity for human FcRn, resulting in 2–5-fold increases in half-life in monkeys and humans [5158]. For example, the analysis of antibodies specific for Staphylococcal α-toxin with the ‘YTE’ half-life extending mutations (Met252 to Tyr, Ser254 to Thr, Thr256 to Glu that are all in proximity to the key residues of IgG that interact with FcRn (Figure 1B) [59]) during phase II clinical trials demonstrated half-lives ranging from 80–112 days, compared to around 20 days for wild type (WT) human IgG1 [52].…”
Section: Fcrn As a Regulator Of The In Vivo Half-lives Of Iggmentioning
confidence: 99%